Current issues in knowledge management - Jennex 1956- (Information Science Reference, 2008)
"This book combines research on the cultural, technical, organizational, and human issues surrounding the creation, capture, transfer, and use of knowledge in today's organizations. Topics such as organizational memory, knowledge management in enterprises, enablers and inhibitors of knowledge sharing and transfer, and emerging technologies of knowledge management, offering information to practitioners and scholars in a variety of settings"--Provided by publisher.